تجليات المكان في رواية الحي الخلفي لمحمد زفزاف (Journal of the College of Basic Education, 2022)
This study and tagged with (the manifestations of the place in the novel The Back Quarter of Muhammad Zafzaf) comes to stand at an important narrative component of the novel work and how the writer employed the element of the place in his novel The Back Quarter, the place is the place or space in which the events of the novel revolve, and the writer tries to harness this element In the service of the rest of the other narrative elements, such as personalities, narrative visions and events, so this study came to stand at the manifestations of this narrative element, so we addressed the threshold of the text which is the title and its link to the significance of the place, as well as the writer’s employing the actions and movements of the characters in describing the place’s image depending on his narrative language, noting some changes in Places can be changed according to the circumstances and conditions of the fictional characters, and their movement from one place to another